Optimization of the Door to Door Sambang Program in Prevention of Criminal Acts of Motorized Vehicle Theft in the Magelang Regional Police Area - Bernardus, Ayub Peter (Advances in Police Science Research Journal, 2020)
This research was conducted using a qualitative approach and field research methods. Where in the collection of data carried out by interview, observation and study of documents in the Magelang Police Station. In analyzing all existing data the Author uses several theories and concepts, namely management theory (George R Terry) and Perkap No. 3 of 2015 concerning Community Policing. Based on the results of research that has been conducted by the Magelang District Police Binmas Unit, the door to door has been implemented. But in its implementation is still not optimal so that the crime rate is still increasing and needs improvement in its implementation. In order for the program to be implemented to its full potential, the leaders put in place a reward and punishment system in order to arouse the motivation of the members in implementing the door to door program. In daily implementation there are factors that influence the implementation of the door to door sambang program. The first factor is that which comes from the internal police station itself, in its implementation there are still found shortages both in terms of human resources, infrastructure and knowledge of the door to door sambang program. The second factor is from the outside, namely the community, the community still does not fully understand this sambaing program and what is its purpose. As a suggestion to the Magelang Police Chief so that the existing shortcomings can be corrected so that the program can run optimally.